PENGARUH PELATIHAN DAN PENGETAHUAN AGROFORESTRI SAWIT TERHADAP KESEJAHTERAAN PETANI DI KECAMATAN SILAT HILIR - adin subara; Stefanus Masiun; Veronika Lidia (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study investigates the effect of oil palm agroforestry training and knowledge on farmers’ welfare in Silat Hilir District. The independent variables are Oil Palm Agroforestry Training (X1) and Oil Palm Agroforestry Knowledge (X2), while the dependent variable (Y) is Farmers’ Welfare. A quantitative approach with multiple linear regression analysis was employed, and data were processed using SPSS version 27. The analysis involved descriptive statistics, validity and reliability tests, normality, multicollinearity, heteroscedasticity tests, as well as t-test, F-test, coefficient of determination (R²), and correlation coefficient analysis. The research findings indicate a simultaneous influence of training and knowledge on farmers’ welfare by 61.8%. This result demonstrates that Oil Palm Agroforestry Training and Knowledge have a significant effect on Farmers’ Welfare. The study emphasizes the importance of enhancing farmers’ capacity through structured training and strengthening knowledge to support sustainable oil palm agroforestry practices and improve farmers’ household welfare. Keywords: agroforestry, farmers’ welfare, training, knowledge